P697 Thiopurines vs. anti-TNFa for the prevention of postoperative recurrence in Crohn's disease—a meta-analysis. (16th January 2018) - Beelen, E M J; Oldenburg, B; van der Meulen-de Jong, A E; Ponsioen, C I J; Dijkstra, G; Pierik, M J; Hoentjen, F; de Boer, N K H; Erler, N S; van der Woude, C J; de Vries, A C
Abstract: Background: Anti-TNFa and thiopurine treatment both reduce the risk of endoscopic recurrence (ER) in postoperative Crohn's disease (CD) patients. As studies comparing the efficacy of thiopurines and anti-TNFa have shown conflicting results, international guidelines do not express a preference for one of both therapies in postoperative CD patients. We aimed to conduct a meta-analysis of available prospective trials. Methods: Embase, Medline, Web of Science, the Cochrane database, and Google scholar were searched for prospective trials comparing anti-TNFa and thiopurine in postoperative CD patients. The primary outcome measure was the proportion of patients with ER, the secondary outcome was clinical recurrence (CR). Comparison of efficacy was done with relative risk (RR) using the MantelHaenszel method with a random-effects model. The methodologic quality of selected trials was assessed using the GRADE approach. Results: Five out of 938 retrieved studies were included (three RCTs, one RCT abstract, one prospective non-randomised trial) with a total of 148 CD patients in the thiopurine group and 111 patients in the anti-TNFa group. Timing of endoscopy varied amongst the studies from 6 to 12 months after ileocolonic resection and ER was defined as ≥i2 or ≥i2b. Three studies were included in analysis for CR. The majority of patients were considered at high risk of postoperative recurrence due to the presence of one or more risk factors (active smoking, penetrating disease, previous resection). Further study and patient characteristics were comparable. Postoperative ER rate was significantly higher in patients treated with thiopurines (51%) as compared with anti-TNFa (25%) (RR 2.41, 95% CI 1.23–4.73, p = 0.01). Postoperative CR was also higher in patients treated with thiopurines as compared with anti-TNFa (RR 2.38, 95% CI 0.91–6.02, p = 0.08), although not statistically significant. The quality of evidence was modelled to be moderate for assessing ER and low for CR. Conclusions: Meta-analysis of available published data suggests that anti-TNFa is superior to thiopurines in the prevention of postoperative ER. However, for a reliable preference in optimal postoperative treatment strategy, individual patient data analysis is required to account for confounding factors (e.g. prior medication, therapy optimisation) and risk factors associated with postoperative CD recurrence.